Slowly Progressive and Painless Thoracic Aortic Dissection Presenting with a Persistent Fever in an Elderly Patient: The Usefulness of Combined Measurement of Biochemical Parameters - Shunsuke Yamada; Masanori Tokumoto; Toshiaki Ohkuma; Yasuo Kansui; Yoshinobu Wakisaka; Yuji Uchizono; Kazuhiko Tsuruya; Takanari Kitazono; Hiroaki Ooboshi (Case Reports in Medicine)
Aortic dissection is a fatal medical condition that requires urgent diagnosis and appropriate intervention. Because acute aortic dissection often manifests as sudden onset excruciating chest pain, physicians can easily reach a proper diagnosis. However, some patients with aortic dissection present with varied clinical manifestations without exhibiting typical chest pain, leading to a delayed diagnosis and possible fatality. We herein present the case of an elderly subject with a fever of unknown origin who was ultimately diagnosed with aortic dissection. In the present case, a negative procalcitonin test, increased D-dimer and serum creatinine phosphokinase-BB levels, and reelevation of the CPR level led us to the correct diagnosis.